Os impactos de anúncios macroeconômicos sobre a volatilidade e a dependência intradiária entre retornos financeiros - Barbosa Júnior, João (2019)
The use of high frequency data has been recently intensified. Many aspects related to finance in general have considered the loads of information that such data provide to scientific studies. One particularly interesting area is the impact assessment of macroeconomic announcements on prices and volatility of financial assets in the period around the ad time. Although there is an extensive literature dealing with the impacts on these announcements on the price and volatility of financial assets, only a few of them assess the impact on the dependency between these assets. The current paper intends to assess the impact of important announcements related to the US economy over the dependence of the euro, pound and Swiss franc exchange rates against the US dollar. On this regard, we use closing price data for these exchange rates, sampled every five minutes, for the period from June 3, 2013 to June 12, 2017.The volatility of the intraday log-returns series is modeled using the MCGARCH (Multiplicative-component Generalized Autoregressive Conditional Heteroskedasticity model) and the dependence between the exchange rates series is modeled by a D-vine copula with time-varying parameters, according to the Generalized Autoregressive Score (GAS) model. We find empirical evidence that, in fact, some macroeconomic announcements impact the dependency between these exchange rates around the ad period.